Relevansi Tasawuf terhadap Krisis Kesehatan Mental: Upaya Integrasi dengan Psikologi Modern - Haq, Muhammad Syauqi Arinal; Masbuang; Saad, Suadi; Wahid, Masykur (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
The global mental health crisis demands a more comprehensive healing approach, particularly within Muslim societies that require harmony between psychological and spiritual dimensions. This study focuses on integrating Sufism and modern psychology as an effort to construct a holistic paradigm of soul healing. The primary objective of this research is to formulate a model of integrative soul healing that addresses the limitations of modern psychology while actualizing the potential of Sufism in responding to contemporary mental health challenges. This research employs a qualitative method using a literature study and interdisciplinary analysis. The primary sources include classical Sufi works, modern psychological theories, and previous studies on the integration of spirituality and mental health. The analysis critically examines Sufi concepts such as tazkiyatun nafs, dhikrullah, and muraqabah, and then correlates them with modern psychological frameworks, including cognitive-behavioral therapy, existential psychology, and positive psychology. The Findings indicate significant common ground between Sufism and modern psychology in their orientation toward inner balance and enhancing well-being, despite epistemological differences. Based on this analysis, the study proposes a Model of Integrative Soul Healing that encompasses three core stages: diagnosis, intervention, and transformation. Hence, this research contributes to the advancement of a holistic Islamic-based therapeutic paradigm applicable in counseling, education, and clinical practice.